Studi Kasus Tindak Pidana Korupsi Terhadap Perhitungan Kerugian Keuangan Negara (Putusan Mahkamah Agung Nomor 1958 K/Pid.Sus/2018) - Citranu Citranu (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2020)
This article aims to determine the authority of calculating state financial losses in cases of corruption in The Supreme Court Of Decision Number 1958 K / Pid.Sus / 2018 and what legal effort can be done by the convicted person to obtain justice. This study uses the normative juridical method which is to examine the problem using the statutory approach and doctrinal approach. The results of this study, which has the authority under the regulation to calculate state financial losses is the BPK or BPKP while the Judicial Review is a legal effort that can be carried out by the convicted person to obtain justice, on the basis of the Panel of Judges or Judex Factie there has been an oversight and overstepped the authority in deciding a case.